Monetary economics - Afolabi, Layi. (Ibadan, Nigeria : Heinemann Educational Books, 1991)
This book covers all the topics in the syllabus for the Nigerian Chartered Institute of Bankers Part II examination. Some of the topics in the book include monetary policies and practices, the banking system, financial intermediation, international economics and international liquidity
Includes index.
osa 16/01/2019
Loans
Keywords: Money; Monetary policy; Financial institutions